Energy consumption, CO2 emissions, and economic growth in the United States, China, and India: A wavelet coherence approach. Issue 5 (August 2020) - Khochiani, Ramin; Nademi, Younes
Climate change is one of the most dangerous threats to human beings, and therefore, it is of great importance for the researchers to inform the policy makers of the threats of climate change and global warming. One of the main causes of climate change is the greenhouse gas emissions, particularly CO2 emissions. In this paper, we try to find a nexus between energy consumption, CO2 emissions, and economic growth in the United States, China, and India, known as three most polluting countries in the world. For this purpose, we applied the wavelet correlation and the partial wavelet coherence approaches during the period 1971–2013. The empirical results for the United States show that the GDP is positively correlated with the CO2 emissions and energy consumption in all frequencies. For China, there is a significant positive relationship between the GDP and CO2 emissions/energy consumption for the short-term horizon. However, for India, although there is a significant positive relationship between the GDP and CO2 emissions, the nexus between the GDP and the energy consumption is not clear. Furthermore, the pollution haven hypothesis was confirmed by the obtained empirical results. Based on our study, we suggest the policy makers in these three countries making supportive decisions for the producers to use modern environment-friendly technologies and renewable energies in their products.